Supervised Physical Therapy Versus Video-Assisted Technique for Chronic Mechanical Low Back Pain: A Comparative Study - Shetty, Spoorthi; KU, Dhanesh Kumar; Chippala, Purusotham (Journal of Health and Allied Sciences NU, 2021)
Objective To compare the effect of supervised physical therapy versus video-assisted technique in patients with chronic mechanical low back pain.Materials and Methods This is a comparative study. Forty-two patients were recruited in the study where they were randomized by simple random sampling. Group A (n = 21) received supervised physical therapy, and Group B (n = 21) received the video-assisted technique. The intervention was given 45 minutes per day for 15 days. The measures of visual analog scale (VAS) and Roland–Morris Disability Questionnaire (RMQ) were taken both at baseline and after 15 days of intervention.Results Comparison between the two groups using Mann–Whitney U test, supervised physiotherapy group showed significant improvement in VAS on activity, RMQ, and RMQ percentage (p < 0.005). However, Group A, VAS on rest was not significant (p > 0.005).Conclusion Supervised physical therapy is effective in reducing pain on activity and improved the disability of patients with chronic mechanical low back pain than the video-assisted technique.
Keywords: mechanical low back pain; supervised physical therapy; home exercise; video-assisted technique